Community-Acquired Acute Kidney Injury at Hospital Admission What Happens One Year After. Issue 6 (2021) - Reis, Marina; Salvador, Pedro; Ventura, Ana; Beça, Sara; Gomes, Ana Marta; Dias, Vitor Paixão; Fernandes, Joao Carlos
No abstract available